The Effect of Promotion and Location on Purchase Decisions in Serpong Karya Cemerlang in Tangerang - Arief Budiyanto (PINISI Discretion Review, 2019)
This study aims to determine the effect of promotion and location on purchasing decisions at PT. Serpong Karya Cemerlang in Tangerang. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination, and hypothesis testing. This study's results significantly affected purchasing decisions by 38.9%; hypothesis testing obtained t count> t table or (7.906> 1.984). The location significantly affects purchasing decisions by 51.4%; hypothesis testing is obtained t count> t table or (10,176> 1,984). Promotion and location simultaneously have a significant effect on purchasing decisions with the regression equation Y = 9.737 + 0.260X1 + 0.506X2 and the contribution of the effect is 55.8%, the hypothesis test obtained F count> F table or (61.338> 2,700).